Understanding the implementation and adoption of an information technology intervention to support medicine optimisation in primary care: qualitative study using strong structuration theory - Jeffries, Mark; Phipps, Denham; Howard, Rachel L.; Avery, Anthony; Rodgers, Sarah; Ashcroft, Darren (BMJ Publishing Group Ltd, 2017)
Objectives: Using strong structuration theory, we aimed to understand the adoption and implementation of an electronic clinical audit and feedback tool to support medicine optimisation for patients in primary care.